2022
DOI: 10.31234/osf.io/t7bpd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active learning-based Systematic reviewing using switching classification models: the case of the onset, maintenance, and relapse of depressive disorders

Abstract: Systematic reviews and meta-analyses are top of the bill in research. However, the screening phase requires an enormous effort in reading and labeling thousands of papers identified via systematic search. Active learning-aided systematic reviewing offers a solution by combining machine learning algorithms with user input to reduce screening load. This study explores the performance of these algorithms and different ways to apply them. This study is divided into four studies evaluating and improving this active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Firstly, the results of simulation studies were applied to new data. For example, which model to use in the first screening phase was decided based on a simulation study performed on a different, smaller, dataset about depression (Teijema et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, the results of simulation studies were applied to new data. For example, which model to use in the first screening phase was decided based on a simulation study performed on a different, smaller, dataset about depression (Teijema et al, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, for the second screening phase, we first used the labeling decisions of the first round to optimize the hyperparameters per topic to receive the optimal hyperparameters for a 17-layer convolutional neural network (CNN) (Teijema, 2021) in combination with a doc2vec feature extractor. This model appeared to have better performance than the default deep learning models available in ASReview as was concluded in a simulation study conducted on similar data (Teijema et al, 2022). Using the optimized hyperparameters, we trained the 17-layer CNN model.…”
Section: Screening Phase 2: Deep Learningmentioning
confidence: 96%
See 2 more Smart Citations
“…Lastly, we could take an even broader view and argue that the set of included records is also allowed to vary as long as the conclusion coming out of the post-processing stage is still the same. Reproducing a systematic review in this way gives confidence that missing a specific record is not essential for the final conclusions; see for an example [33].…”
Section: Reproducibility In the Three Phasesmentioning
confidence: 99%